Microscale Rearrangement of Ammonium Induced by Snow Metamorphism - Trachsel, Jürg C.; Avak, Sven E.; Edebeli, Jacinta; Schneebeli, Martin; Bartels-Rausch, Thorsten; Bruetsch, Sabina; Eichler, Anja (Frontiers in Earth Science, 2019)
Earth’s snowpack hosts chemical impurities that exchange with the overlying air, strongly impacting atmospheric chemistry. Being embedded in firn and glacier ice formed from surface snow, impurities provide the basis for reconstructing past atmospheric composition from ice core records. The location of these impurity compounds within the snow critically controls their reactivity and preservation. Ammonium (NH4+) determines acid-base equilibria and buffer capacity within the snow and is a fundamental ice-core proxy, especially for biogenic, forest fire, and anthropogenic emissions. However, the redistribution during snow metamorphism affecting snow chemical reactivity and potential post-depositional relocation is not understood so far. Here, we study the rearrangement of NH4+ and five other major ions (Ca2+, Cl–, F–, Na+ and SO42–) during dry snow metamorphism using a series of elution experiments. Artificial and natural snow samples were stored for up to three months at a controlled temperature gradient of 40 K/m and isothermal conditions. The different types of snow increase complexity as natural and artificial snow have a different history that impacts their physical properties and the initial distribution of impurities. Further, we test our findings using natural snow samples taken from different depths of a natural snowpack at the Weissfluhjoch (Swiss Alps) to confirm the impact of our laboratory results to the cryosphere. With progressing temperature gradient metamorphism, snow structures in natural and artificial snow converged and ions with high solubility in ice (NH4+, F- and Cl-) were incorporated into the less accessible ice interior. In contrast, ions with lower solubility (Ca2+, SO42- and Na+) became better accessible for the eluent. Our results show that the redistribution during snow metamorphism is strongly dependent on the temperature gradient, exposure time and chemical composition. This study allowed for the first time to explicitly relate the general low relocation proneness of NH4+ during post-depositional processes such as meltwater percolation to the preferred incorporation of this ion into the less accessible ice interior during snow metamorphism. Furthermore, our results imply that with ongoing aging of a snowpack, NH4+, independent of its primary location, is less available for chemical reactions at the air-ice interface.